Factors associated with self-management behaviors among Chinese adults with ischemic stroke: A cross-sectional study - Chen, Xiaoxiao; Samartkit, Niphawan; Masingboon, Khemaradee (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: In China, adults with ischemic stroke are getting younger. Additionally, following a stroke, they often neglect self-management (SM), which significantly impacts the rehabilitation process and treatment outcomes. Objective: This study aimed to describe SM behavior and examine the relationship between stroke prevention knowledge, life stress, family relationships, and SM behavior among adults with ischemic stroke. Methods: A total of 125 participants were recruited between October 2022 and March 2023 based on defined inclusion criteria. Research instruments included a demographic questionnaire, the Stroke Self-management Behavior Scale for Young Adults, the Stroke Prevention Knowledge Questionnaire, the Perceived Stress Scale, and the Brief Family Relationship Scale. Data were analyzed using descriptive statistics and Pearson’s product-moment correlation. Results: The mean score of SM behavior was 88.1 out of 130 (SD = 16.5). Stroke prevention knowledge and family relationships showed a moderate positive significant relationship with SM behavior (r = 0.39, r = 0.34, p <0.001, respectively). Life stress had a significant negative relationship with SM behavior (r = -0.33, p <0.001). Conclusion: The findings offer insights for nurses to develop nursing interventions to promote SM behavior among adults with stroke. Furthermore, they can assist hospitals in transitioning care to the community by emphasizing holistic nursing practices that educate about stroke prevention knowledge, encourage family support, and provide stress management strategies to enhance the SM abilities of adults with stroke.